Network formation with closeness incentives - Berno Buechel (Bielefeld University, Institute of Mathematical Economics (IMW), 2007)
We study network formation in a strategic setting where every agent strives for short paths to the other agents. The main parameter of our model is the marginal rate of substitution between network benefits and linking costs. We provide boundaries of stable networks for increasing and decreasing marginal returns. The formulated model stands in strong relation to the famous connections model (Jackson & Wolinsky '96): we show that for certain parameter values both models induce the same network structures.
urn:nbn:de:hbz:361-13672
Keywords: 330; Networks; Closeness centrality; Connections; Decreasing returns; Increasing returns